A clinical trial of dextromethorphan in amyotrophic lateral sclerosis - Ole Gredal; Lene Werdelin; S. Bąk; Peter Brøgger Christensen; Gudrun Boysen; Michael Kristensen; Jesper Jespersen; Lisbeth Regeur; H H Hinge; Troels S. Jensen (2009)
Introduction - Although the cause of amyotrophic lateral sclerosis (ALS) is unknown, excitotoxicity mediated by glutamate has been implicated. Dextromethorphan is a NMDA-glutamate receptor antagonist with neuroprotective properties. Material and methods - The effect of treatment with dextromethorphan (150 mg daily) in ALS patients was evaluated in a randomized, double-blind, placebo-controlled study. Forty-five patients were included in the analysis. Results - At the end of the treatment period, 12 months after randomization, 15 patients (65%) in the placebo group and 12 patients (55%) in the dextromethorphan group were still alive (log rank test, P=0.49). Rates of disease progression, as expressed by rates of decline in pulmonary function and in functional disability, were similar in both groups except for a significantly less pronounced rate of decline in the ability scores for the lower extremities in the dextromethorphan group. Conclusion - Treatment with a relatively low dose of dextromethorphan did not result in an improvement in 12-month survival in ALS.